Comparing Feed Intake, Digestibility, Growth and Economic Gain of Horro and Washera Sheep Breeds Fed Wheat Straw Basal Diet Supplemented With Effective Microorganisms Treated Wheat Straw and Concentrate Mixture - Desalegn Tesfaw; Shashie Ayele; Melese Gashu (Veterinary Medicine and Science)
ABSTRACT Background and Objectives An experiment was conducted to compare Horro and Washera sheep in terms of feed intake, digestibility, body weight gain and economic feasibility fed untreated wheat straw (UTWS) a basal diet and supplemented with an effective microorganism‐treated wheat straw (EMTWS) and concentrate mixture (CM). Materials and Methods A total of 10 from each sheep breeds and 2 supplement amounts of EMTWS, supplemented at 10% (A1) and 15% (A2) of the total dry matter intake (TDMI), were arranged in a 2 × 2 factorial treatment arrangement in a completely randomized block design. The sheep of each breed were blocked on the basis of their initial body weights into five blocks of four animals in a block (two animals from each sheep breed), and treatment feeds were randomly allocated within a block during the 100 experimental days. Daily feed intake and body weight at the 10‐day interval were recorded, and data were analysed using general linear model procedures (PROC GLM) of SAS software program. Results The crude protein (CP) content of EMTWS showed only a 1% increment over UTWS, whereas its neutral detergent fibre (NDF) and acid detergent fibre (ADF) values showed a 10% reduction over UTWS. Washera sheep consumed 40 g more TDM over Horro sheep. Sheep fed the A2 supplement consumed 86 g more (p < 0.0001) TDM over A1‐fed sheep. Consequently, Washera sheep and sheep fed‐A2 gained 1 and 3 kg of additional body weight by growing 11 g/day and 33 g over Horro sheep and those sheep fed‐A1, respectively. Sheep fed‐A2 and Washera sheep gave better economic returns than A1‐fed sheep and Horro sheep, respectively. Conclusion Therefore, from the results of the study, it could be suggested that rearing Washera sheep by supplementing 15% EMTWS along with a CM can be recommended for smallholder farmers.